Pelatihan Pembuatan Media Edukasi dalam Upaya Pencegahan Stunting di Desa Lampeji Kecamatan Mumbulsari Kabupaten Jember - Astuti, Soekma Yeni; Setyari, Agustina Dewi; Didik Suharijadi; Sampurna, Hadi; Aji, Fajar; Ummiyyah, Zahratul; Winarni, Retno (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Stunting is an obstacle to the nation's progress because if there are no strategic efforts to prevent and reduce the numbers. The role of the media today is vital because it is one of the elements incorporated in the Penta helix that accelerates the reduction. This service aims to use the press to reduce stunting rates through educational products. The method involves four steps: planning, socialization, mentoring training, and mentoring stages. The planning stage consists of preparation, observation, problem mapping, and preparation of a mentoring plan. The mentoring stage consists of two steps: making educational videos and Focus Group Discussions (FGDs). The results of this study show that the media plays a strategic role in efforts to prevent the increase in stunting rates. This is done by actively involving the community in contributing to making educational videos that focus on the issue of stunting, especially in the Lampeji village area, Mumbulsari District, Jember Regency.